Wheat Response to Application Methods and Levels of Nitrogen Fertilizer: I. Phenology, Growth Indices and Protein Content - Ullah, Ghazanfar; Khan, Ejaz Ahmed; Awan, Inayat Ullah; Khan, Muhammed Ayyaz; Khakwani, Abdul Aziz; Baloch, Muhammed Safdar; Khan, Qudrat Ullah; Jilani, Muhammad Saleem; Wasim, Kashif; Javeria, Sadaf; Jilani, Ghulam (Pakistan Journal of Nutrition, 2013)
Fertilizer use efficiency of nitrogen is very low due to various types of losses. This two year field experiment was carried out to investigate the effect of various levels of nitrogen and its application methods on phenology, growth indices and quality of wheat. Fertilizer application methods (broadcast and side-dressing) were placed in the main plots, while nitrogen levels (60, 90, 120, 150, 180 and 210 kg/ha) applied in sub plots. Crop data showed that nitrogen methods had non-significant effect on phenology, physiology and quality parameters. Fertilizer application rates rendered significant effect on various parameters except days to emergence. Nitrogen at 210 kg/ha gave significant increase in the phenological and growth parameters. Leaf area index and leaf area duration were significantly affected by the rate of nitrogen fertilizers. Protein contents were also increased by the application of higher amount of nitrogen. Interaction among application methods and nitrogen levels showed significant variations in net assimilation rate, while crop growth rate remained significant in the second year and protein content had shown significant variation during the first year of study.